Optimal Portfolio Analysis Using The Markowitz Model - Zuhra, Diza Isnani; Matyani, Matyani; Sofyaun, Ashari (Universitas Syiah Kuala, 2025)
The purpose of this study is to determine the optimal portfolio using the Markowitz model approach. Secondary data used in this study are in the form of a list of company stock prices on IDXBUMN20 and SRI-KEHATI on the Indonesia Stock Exchange. There are several research findings including the variance of stock returns between groups is not significantly different. There is no significant difference in variance between groups in stock risk data. There is no significant difference in the average stock return between the groups being compared. There was no significant difference in average stock risk between groups.